Saving Frozen Embryos Through Adoption Agreements: Bridging The Legal & Bioethical Gap in Indonesian Private Civil Law - Dewi Padusi Daeng Muri; Irawan Soerodjo; Carolus Boromeus Kusmaryanto; Putra Hutomo (Law Development Journal, 2026)
This study examines the legal and bioethical issues surrounding remaining frozen embryos in Indonesia, particularly the lack of regulations governing their use through embryo adoption. Current regulations require the destruction of unused embryos, creating a legal and ethical dilemma as embryos are considered potential human life with a right to life. This study uses a socio-legal approach with legal and comparative analysis to evaluate existing regulations and practices across several countries. The findings indicate a significant legal gap in Indonesia regarding embryo adoption, resulting in a lack of legal protection for prospective parents and embryos. This study proposes embryo adoption as a viable legal and bioethical solution to ensure embryo protection and the fulfillment of reproductive rights, and contributes to the development of a more comprehensive legal framework in private civil law.